2021
DOI: 10.3390/cancers13205129
|View full text |Cite
|
Sign up to set email alerts
|

In the Era of Systemic Therapy for Hepatocellular Carcinoma Is Transarterial Chemoembolization Still a Card to Play?

Abstract: Conventional transarterial embolization (cTACE) has been proven to be effective for intermediate stage hepatocellular carcinoma (HCC), with a recent systematic review showing an overall survival (OS) of 19.4 months. Nevertheless, due to the rapid development of the systemic therapeutic landscape, the place of TACE is becoming questionable. Is there still a niche for TACE in the era of immunotherapy and combination treatments such as atezolizumab–bevacizumab, which has shown an OS of 19.2 months with excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…Others include immunotherapeutic agents such as ipilimumab, nivolumab, and pembrolizumab [ 235 , 236 , 237 ]. A majority of the studies have shown positive results, with improved outcomes and acceptable safety profiles [ 238 ].…”
Section: New Developments and Future Directionsmentioning
confidence: 99%
“…Others include immunotherapeutic agents such as ipilimumab, nivolumab, and pembrolizumab [ 235 , 236 , 237 ]. A majority of the studies have shown positive results, with improved outcomes and acceptable safety profiles [ 238 ].…”
Section: New Developments and Future Directionsmentioning
confidence: 99%
“…Recently, the Up-to-seven criteria, which the total number of tumors and the largest tumor size (measured in cm) does not exceed 7, was introduced among HCC BCLC stage B [6]. Up to now, strategy of treatment of HCC stage B has changed quickly, however there is currently no speci c optimal treatment method [7].…”
Section: Introductionmentioning
confidence: 99%
“…Transarterial chemoembolization (TACE) is the most widely used treatment method for intermediatestage hepatocellular carcinoma (HCC) that is not suitable for curative treatment, and it is the rst choice for patients in the BCLC stage B subgroup [4,7]. TACE includes traditional lipiodol-based TACE and drugeluting bead TACE (DEB-TACE).…”
Section: Introductionmentioning
confidence: 99%